Transcription Factor Based Small‐Molecule Sensing with a Rapid Cell Phone Enabled Fluorescent Bead Assay. Issue 48 (18th September 2020) - Chern, Margaret; Garden, Padric M.; Baer, R C.; Galagan, James E.; Dennis, Allison M.
Abstract: Recently, allosteric transcription factors (TFs) were identified as a novel class of biorecognition elements for in vitro sensing, whereby an indicator of the differential binding affinity between a TF and its cognate DNA exhibits dose‐dependent responsivity to an analyte. Described is a modular bead‐based biosensor design that can be applied to such TF‐DNA‐analyte systems. DNA‐functionalized beads enable efficient mixing and spatial separation, while TF‐labeled semiconductor quantum dots serve as bright fluorescent indicators of the TF‐DNA bound (on bead) and unbound states. The prototype sensor for derivatives of the antibiotic tetracycline exhibits nanomolar sensitivity with visual detection of bead fluorescence. Facile changes to the sensor enable sensor response tuning without necessitating changes to the biomolecular affinities. Assay components self‐assemble, and readout by eye or digital camera is possible within 5 minutes of analyte addition, making sensor use facile, rapid, and instrument‐free. Abstract : The allosteric transcription factor TetR acts as a sensor and actuator in this quantum dot enabled fluorescent bead assay for the small molecule anhydrotetracycline. This rapid, antibody‐free biosensor produces a visible change in fluorescent color, which can be detected by eye or with an inexpensive digital camera, based on dose‐dependent analyte‐responsive protein‐DNA binding. The adaptable sensor uses easily accessible biomolecular components.